Urbanization is associated with increased breeding rate, but decreased breeding success, in an urban population of near-threatened African Crowned Eagles. (20th May 2020) - Muller, Rebecca; Amar, Arjun; Sumasgutner, Petra; McPherson, Shane C; Downs, Colleen T
Abstract: Urban areas can be attractive to certain species because of increased food abundance and nesting availability, which in turn may increase productivity or breeding rates. However, there are also potential costs associated with urban living such as higher nest failure, poorer body condition, or increased prevalence of disease. These costs may result in species trading off the number of young produced against the condition of their young. African Crowned Eagles ( Stephanoaetus coronatus ) are a rare example of large, powerful apex predators that breed in some urban areas in Africa. In this study, we explored the breeding performance of these eagles across an urbanization gradient in KwaZulu-Natal Province, South Africa, over 7 breeding seasons. We predicted that living in an urban environment would increase productivity through an increase in breeding rate (shifting from typically biennial breeding to annual breeding). We then explored if there were any hidden costs associated with such a change in breeding strategy by examining the body condition of chicks from pairs that had successfully bred in the previous year. We found that pairs in more urban areas were more likely to breed annually, resulting in higher breeding rates, but were also less likely to successfully fledge a chick (i.e. lower breeding success). These 2 contrasting responses counteracted each other and resulted in similar productivity across the urbanization gradient. For those eagles that bred in consecutive years, annual breeding did not appear to have a negative cost on chick condition. The switch to annual breeding is thought to be a response to improved or more constant food sources in urban areas, while higher failure rates might be because of increased nest disturbances from anthropogenic sources (e.g., vegetation clearing, development of industrial areas, human and car traffic). However, although urbanization negatively affected the breeding success of African Crowned Eagles, they are able to persist and thrive in this highly transformed environment, likely through an increased breeding rate. Graphical Abstract: Lay Summary: One species that is hardly recognized as an urban adapter is the Crowned Eagle in the metropoles of Durban and Pietermaritzburg, South Africa. We explored the breeding performance of Crowned Eagles across different levels of urbanization, and specifically teased apart breeding rate (i.e. if an eagle breeds annually or every other year) and breeding success (i.e. if they fledge a young or not in a given year). We showed that Crowned Eagles change their breeding strategy in urban areas by increasing their breeding rate, but found nest failures occurred more often at more urbanized sites. These contrasting responses counteracted each other and resulted in similar productivity across the urbanization gradient and highlighted the value of long-term data.